Frequency control capability of wind turbine under different operation status. Issue 13 (12th December 2017) - Zhu, Chen; Bi, Tianshu; Yang, Libin; Li, Chunlai; Yang, Jun; Xu, Guoyi
Abstract : To secure safe operation of the power system with high wind power penetration, variable speed wind turbines (WTs) are required to provide ancillary services like system frequency support to the power system. This study focuses on the different frequency control strategies and the amount of available additional active power of WT under different operation status. Additional control strategies for WT are presented considering different operating characteristics. Then WT frequency control capability under two typical operation status with different control methods is quantified and the methods to determine the controller parameter values are proposed to fully utilise the WT's available frequency control capability. The performance of the strategies is validated in Matlab/Simulink. The results indicate the reduction in the rate of change of frequency and frequency nadir which can ensure the safe operation of the WTs and the power system.